Sekwencjonowanie obiektów uczących w inteligentnych systemach nauczania na odległość - Abramowicz, Witold; Kaczmarek, Tomasz; Kowalkiewicz, Marek (Learning object sequencing, 2005)
Different e-leaming technologies use learning objects as knowledge resources. The methodologies of designing learning objects focus on creating single learning objects. Most of them neglect the representation of dependencies between learning objects. The research pursued on this topic led to several solutions of the problem. None of them however is well suited for distance education in the Internet environment. Such a solution is necessary to develop methods of automatic sequencing of learning objects. In this article the authors propose a solution based on directed acyclic graphs and graph algorithms for creating such learning paths, that can be easily adopted for distance learning on the Internet. Learning objects and the dependencies between them are represented as paths in the graph. This enables reasoning based on the graph structure about the learning paths adapted for specific user requirements. The authors propose also a method of semi-automatic creation of dependencies between learning objects grounding on the knowledge extracted form the learning objects.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 13-22